THE INFLUENCE OF SERVICE QUALITY, FOOD QUALITY, AND PRICE TOWARD CUSTOMER SATISFACTION AT COFFEE LOCA MEDAN - Vienny Kwosierra; Arifin Arifin (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2022)
Customer satisfaction is a critical component in guaranteeing the restaurant's long-term sustainability. The data acquired from Coffee Loca demonstrates that it is unable to sustain the stability of its number of customers, indicating that customer satisfaction at Coffee Loca is insufficient. As a result, Coffee Loca must enhance all factors that might affect customer satisfaction, including service quality, food quality, and price. The objective of this research is to analyze the influence of service quality, food quality, and price on customer satisfaction at Coffee Loca. The population of this research is 163 customers of Coffee Loca. Convenience sampling is utilized, and the number of samples obtained is 116 respondents. The multiple linear regression approach is used to analyze the data. All hypotheses proposed in this research are accepted. The result of the analysis shows that service quality has a significant positive influence on customer satisfaction, food quality has a significant positive influence on customer satisfaction, the price has a significant positive influence on customer satisfaction, and service quality, food quality, and price have a positive and significant influence on customer satisfaction simultaneously. In terms of service quality, it is recommended that Coffee Loca improves its serving time and accuracy, provides kids-friendly food, and trains its employees regarding their menus and hygiene. In terms of food quality, it is recommended that Coffee Loca serves food with an appetizing shape, color, and taste. In terms of price, it is recommended that Coffee Loca improves its price competitiveness.